Do stress tests matter? Evidence from the 2014 and 2016 stress tests - Oana-Maria Georgescu; Marco Gross; Daniel Kapp; Christoffer Kok (European Central Bank (ECB), 2017)
Stress tests have been increasingly used in recent years by regulators to foster confidence in the banking sector by not only increasing its resilience via mandatory capital increases but also by enhancing transparency to allow investors to better discriminate between banks. In this study, using an event study approach, we explore how market participants reacted to the 2014 Comprehensive Assessment and the 2016 EBA EU- wide stress test. The results show that stress test disclosures revealed new information that was priced by the markets. We also provide evidence that the publication of stress test results enhanced price discrimination as the impact on bank CDS spreads and equity prices tended to be stronger for the weaker performing banks in the stress test. Finally, we provide some evidence that also sovereign funding costs were affected in the aftermath of the stress test publications. The results provide insights into the effects and usefulness of stress test-related disclosures.
Keywords: G14; G18; G21; 330; event study; bank stress tests; disclosure